The Evaluation of the Occurrence of the Oral Focal Infection. The Group of 278 Patients - M. Chalupová; H. Hecová (Czech Dental Chamber, 2016)
Introduction and aims: Focal infection is defined as a type of disease when the chronic disease arises in the remote organ or tissue from the primary locus of the infection. The aim of this retrospective study is to assess the prevalence of oral focal infection in 278 patients sent with a request to define a possible risk of local infection in the oral cavity. Methods: In the medical documentation, we have found 278 patients referred to the Dental Clinic, University Hospital in Pilsen since 2011, for the exclusion of oral focal infection. The patients' oral health status, the presence of the teeth suspected of dental focal infection, the need for conservative, periodontal and oral surgery rehabilitation was evaluated. Results: The group of 278 patients was divided into two groups. Group A consisted of 19 patients who were referred to the dental clinic with a request for confirmation or exclusion of oral focal infection as a source of the patient`s disease. Group B consisted of 259 patients referred to the dental clinic within the preoperative medical assessment. On the basis of the documentation, the state of teeth and periodontium and the need for subsequent therapy was retrospectively assessed.In Group A, rehabilitated dentition was observed in only three patients (15.8%). Occurrence of focal infection of oral origin was diagnosed in 15 patients (78.9%), 12 patients were recommended to extract the teeth. Conservative periodontal treatment was required in for 16 patients (84.2%).In Group B, rehabilitated teeth were found in 35 patients (13.5%), focal infection of oral origin was found in 145 patients (56%). In 129 patients (49.8%) at least one tooth extraction was necessary. Conservative treatment of periodontium was necessary in 175 patients (67.6%). Conclusion: Our study evaluated that the oral health status of the majority of patients investigated for possible occurrence of infection in the oral cavity was insufficient. The results showed that it is necessary to raise awareness among the population about the importance of the impact of oral health on overall health.